Use of Coloured Petri Net models in planning, design, and simulation of intelligent wireless medical device networks for safe and flexible hospital capacity management. (7th May 2007) - Sloane, Elliot B.; Gehlot, Vijay
US hospitals often now operate at full capacity, frequently causing incoming ER patients to be staged in ER hallways or detoured to more distant facilities. The process of moving patients from the ER is complex, requiring matching of resources to the unique hour-to-hour mixture of patients and illnesses in the enterprise. Some hospitals are adapting 'lean manufacturing' techniques by using wireless patient monitors to allow flexible creation and reconfiguration of 'Virtual Intensive Care Units (VICUs)' to match changing demands. Unfortunately, wireless medical devices cannot be deployed carelessly because radio- and data-interference and capacity limitations can create patient monitoring safety problems. This paper describes using Coloured Petri Net (CPN) formal simulation modelling tools to perform wireless medical network pre-planning and ongoing configuration management. CPN models can be part of an effective Verification and Validation (V&V) process for wireless medical devices in VICUs to ensure patient safety while meeting clinical capacity demands.